Twelve reasons why boards and executives should be clear that profit is not the purpose of their company. Issue 175 (10th May 2021) - Kravatzky, Axel; Stephens, Mark
Abstract : Leaders of companies are increasingly expected to ensure that their companies fulfill a purpose beyond profits. Many still have doubts, and privately believe the real purpose of the company is simply to make a profit. Here, Dr. Axel Kravatzky and Mark Stephens summarize twelve arguments why profit alone is not, cannot, and ought not be purpose of a company .